2010
DOI: 10.1007/s12263-010-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in Nociceptin/Orphanin FQ-induced food intake in strains derived from rats prone (WOKW) and resistant (Dark Agouti) to metabolic syndrome: a possible involvement of the cocaine- and amphetamine-regulated transcript system

Abstract: Our previous study found that when injected with Nociceptin/Orphanin FQ (N/OFQ) into the brain, male Dark Agouti (DA) rats, which are resistant to metabolic syndrome, have greater hyperphagia than male Wistar Ottawa Karlsburg W (WOKW) animals, which are prone to this disease. We attributed this difference to the fact that these two strains have different cocaine-amphetamine regulated transcript peptide (Cart) gene sequences and expression. In order to address this hypothesis, the present work focused on sex di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Additionally, N/OFQ might induce hyperphagia by inhibiting the endogenous cocaine and amphetamine-regulated transcript (CART) [ 231 , 232 , 233 ], which is another anorectic peptide also regulated by leptin [ 234 ]. Beyond the modulation of these hypothalamic mechanisms, N/OFQ modulates the activity of 5-HT neurons in the DRN (see above) which may also change feeding responses.…”
Section: Role Of the N/ofq-nop System In The Regulation Of Feeding And Food-related Disordersmentioning
confidence: 99%
“…Additionally, N/OFQ might induce hyperphagia by inhibiting the endogenous cocaine and amphetamine-regulated transcript (CART) [ 231 , 232 , 233 ], which is another anorectic peptide also regulated by leptin [ 234 ]. Beyond the modulation of these hypothalamic mechanisms, N/OFQ modulates the activity of 5-HT neurons in the DRN (see above) which may also change feeding responses.…”
Section: Role Of the N/ofq-nop System In The Regulation Of Feeding And Food-related Disordersmentioning
confidence: 99%
“…Interestingly, there are sex differences in CART peptide expression and function (Fagergren and Hurd, 1999, Rondini et al, 2004, Balkan et al, 2006, Gozen et al, 2007, Xu et al, 2010, Battistoni et al, 2011, Gerrits et al, 2011, Hostetler et al, 2011, Rodrigues et al, 2011, Bloem et al, 2012). Because of the findings that there are sex differences in (a) the effects of cocaine on DA in the NAc and (b) in CART peptide expression and function, we explored if there are sex differences in the effects of CART peptide on cocaine-induced LMA in rats.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 30 out of 79 genes (38.0%) with rare variants significantly associated with 46 traits were reported association with some of them in the literatures. For example, PNOC which was associated with the 46 traits (p-value ≤ 1.63 × 10 −12 ), HOMA-IR (p-value ≤ 1.2 × 10 −7 ) and triglycerides (p-value ≤ 9.15 × 10 −9 ) was reported to be associated with insulin resistance [ 60 ] and triglycerides [ 61 ]. MIR409 which was associated with the 46 traits (p-value ≤ 2.77 × 10 −10 ), weight (p-value ≤ 1.65 × 10 −6 ), Hip (p-value ≤ 7.19 × 10 −7 ) and total lean mass (p-value ≤ 2.15 × 10 −6 ) was used as a weight loss biomarker [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Throughout this section, all p-values were calculated using QRFCCA. PNOC which was associated with the 46 traits (p-value ) was reported to be associated with insulin resistance 64 ) was used as a weight loss biomarker. 66 GAPDH which showed an association with the 46 traits (p-value ) was reported to be associated with creatinine.…”
Section: Application To Real Data Examplesmentioning
confidence: 99%